2018
DOI: 10.1371/journal.pone.0205438
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional resilience in Nepal following the earthquake of 2015

Abstract: BackgroundThe 2015 earthquake in Nepal caused massive damages and triggered relief activities to minimize human suffering. The post-earthquake nutrition and food security situation in the hardest hit areas remains uncertain.MethodsTwo national cross-sectional surveys were conducted in 2014 and 2016 among households (HH) with pre-school aged children or newly married women. Of the 21 village development committees (VDCs) included in this sample, 7 fell within “earthquake-affected” areas. This paper presents dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 16 publications
2
10
1
1
Order By: Relevance
“…The prevalence of wasting of 2.5% in 2017 was lower than that of 4.2% in a survey conducted in this province in 2016 [9]. Our findings of decrease in wasting is also similar to a household survey that reports the prevalence of wasting, 4.5% in 2014 and 2.1% in 2016 in seven earthquake-affected areas in Nepal [11]. We found the proportion of underweight children increased from 10.9% in 2015 to 14.0% in 2017 and stunting rose from 26.7 to 31.9% over the period.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The prevalence of wasting of 2.5% in 2017 was lower than that of 4.2% in a survey conducted in this province in 2016 [9]. Our findings of decrease in wasting is also similar to a household survey that reports the prevalence of wasting, 4.5% in 2014 and 2.1% in 2016 in seven earthquake-affected areas in Nepal [11]. We found the proportion of underweight children increased from 10.9% in 2015 to 14.0% in 2017 and stunting rose from 26.7 to 31.9% over the period.…”
Section: Discussionsupporting
confidence: 84%
“…These figures are comparable with the data of the Nepal Demographic and Health Survey 2016, which shows the proportion of underweight children was 13.3% and stunting was 29.4% in Bagmati province, where Bhaktapur Municipality lies [9]. We found a higher proportion of children with stunting (26.7% in 2015 and 31.9% in 2017) than the report that analyses the nutritional status of children in 2014 (23.1%) and 2016 (21.6%) in seven earthquake-affected areas [11]. We also found that being underweight was correlated with the age of the children in 2017.…”
Section: Discussioncontrasting
confidence: 53%
“…One VDC each in the mountains and hills were also assessed, but not addressed in this report (S1 Fig). [9–11] Thus, the present study focuses on generating representative estimates of tooth loss and damage in the Tarai zone, where ~60% of the population of Nepal resides.…”
Section: Methodsmentioning
confidence: 99%
“…37 Within country, while the sample frames and sampling methods were different among the NDHS, 21 PoSHAN, 11 and the National Micronutrient Status surveys, 33 their narrow range of estimates, between 34% and 37%, provides strong corroborative evidence for this plateau phenomenon. Reasons for the plateau have not been formally identified, and the consequences of the 2 national shocks that occurred in 2015—a massive earthquake with its series of aftershocks devastated much of the central hills in April to May, 15 followed by an economic blockade along the Indian border in the last quarter of 2015 that severely affected trade 14 —may yet unfold. While there is some evidence that the national and international response in the year that followed the quake may have mitigated an expected deterioration in nutritional status of children, 15 nutritional consequence of the blockade that also precipitated protests throughout the Tarai has not been reported, although it remains a plausible stress.…”
Section: Discussionmentioning
confidence: 99%
“…12 Thereafter, major national shocks were encountered in 2015 in the forms of a devastating earthquake and economic blockade on the border with India. 13 -16…”
Section: Introductionmentioning
confidence: 99%